PERILAKU NASABAH TERHADAP LAYANAN MOBILE BANKING PERBANKAN SYARIAH: EKSTENSI TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN THEORY OF PLANNED BEHAVIOR (TPB) - Nonah Siti Rojanah, - (2020)
The purpose of this study in general is to test the theory of Technology acceptance Model (TAM) and Theory of Planned Behavior (TPB), namely to analyze the effect of perceived ease of use on perceived usefulness, perceived usefulness and perceived ease of use on customer attitudes, then analyze the effect of customer attitudes towards mobile banking, subjective norms, and perceived behavioral control on intention of using mobile banking and its implications towards the behavior of using mobile banking in Islamic bank customers. In addition, this study also aims to analyze how the effect of spiritual motivation level on intentions of using mobile banking. The population in this study is Islamic bank customers who use mobile banking application services. The sampling technique used was purposive sampling with a total sample of 100 people. The method used in this research is the quantitative method with a causality approach. The data analysis technique used is Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results of this study indicate that the perceived ease of use has a positive and significant effect on perceived usefulness, then perceived usefulness and perceived ease of use have a positive and significant effect on customer attitudes, then the customer attitude towards mobile banking, perceptions of behavioral control and spiritual motivation level have a positive and significant effect on intention of using mobile banking and have implications for behavior of using mobile banking. However, the subjective norm has a negative and not significant effect on the intention of using mobile banking. This research is expected to provide benefits for stakeholders of Islamic banking in Indonesia and provide the information needed in an effort to increase the use of mobile banking of sharia banking in Indonesia. Keywords: mobile banking, technology acceptance model, theory of planned behavior, spiritual motivation level.